Alkaline phosphatase and lactate dehydrogenase enzyme activity in gingival crevicular fluid during orthodontic tooth movements - Baratam Srinivas; Vijay Yannawar; Subhrajit Rana; Mohd Adil Nayeem; K Neha; Debarshi Bhattacharjee; Abhishek Singh Nayyar (Wolters Kluwer Medknow Publications, 2017)
Background: Bone remodeling is a biologic process involving an acute inflammatory response in periodontal tissues during orthodontic tooth movement. The early response of periodontal tissues to mechanical stress involves metabolic changes that allow tooth movement. Aim of the Study: The aim of the present study was to evaluate the changes in alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) enzyme activity in gingival crevicular fluid (GCF) when forces are applied during initial alignment (Phase 1 [P1]) and retraction (Phase 2 [P2]). Settings and Design: The study was performed in a hospital-based population with an experimental design. Materials and Methods: A total of 17 patients (11-21 years) were included in the study, all requiring first premolar extractions undergoing fixed orthodontic treatment. Maxillary canine and mandibular second molar were used as test tooth (TT) and control tooth (CT) in each patient, respectively. On the 14th day after the start of each phase, 2 μL of GCF was collected from mesial side of both TT and CT for ALP and LDH activity determination using spectrophotometer. Statistical Analysis: Statistical analysis was performed with SPSS (version 13, SPSS Inc., Chicago, USA) package. The significance of differences in both phases at test or, at control site for LDH and ALP enzyme activity, was evaluated by performing Student's paired t-test. The significance of differences in between test and control sites in each phase separately was evaluated by performing Student's unpaired t-test. Results: There was a variation in enzyme activity during orthodontic tooth movement. At TT, there was statistically significant increase in ALP and LDH activity in P2 as compared to P1 with P = 0.005 and P < 0.001, respectively. At CT, there was no statistically significant difference in ALP and LDH activity in P1 and P2 with P = 0.054 and P = 0.061, respectively. Conclusion: This study concluded that ALP and LDH activity could be successfully estimated in the GCF, and ALP and LDH activity in GCF reflects the biologic activity in the periodontium during orthodontic tooth movements.